Vanishing Flocks and Shifting Livelihoods: Understanding the Decline and Future Prospects of Sheep Farming in Highland Community of Bhutan (SAARC Journal of Agriculture, 2026)
Sheep farming continues to thrive across most of the nation despite the enormous challenges. However, in the past decade, the practice of sheep farming has completely disappeared in two highland blocks of Gasa district in Bhutan. Therefore, to identify the causes of sheep farming cessation and to analyse future acceptability to revive the sheep farming, a cross-sectional, community-based study was conducted in the Laya and Lunana blocks of northern Bhutan from August 2019 to February 2020. The study employed set of semi-structured questionnaires including household surveys, free-listing challenges faced in sheep farming to capture quantitative information. A total of 132 households (67 hh from Laya and 65hh from Lunana blocks were obtained using Cochran’s formula and respondents were face to face interviewed. The survey revealed that the majority of household in Lunana (91%) relied more on cordyceps compared to those in Laya (70%). However, Laya found to have more diversified income sources. Furthermore, the study identified low economic return (Lunana) and the presence of poisonous plants (Laya) as two major issues that has attributed to cessation of sheep farming. Overall, the majority (Laya=75%; Lunana=95%) of the respondents were not willing to revive sheep farming. Therefore, this study suggests that the sheep farming and its revival in study areas is not viable. Furthermore, it is recommended to conduct research to identify the intervention to transform sheep farming into economic viable enterprise for its revivable and sustainability. SAARC J. Agric., 23(2): 273-283 (2025)